EXPORT OF LABOR RESOURCES FROM KYRGYZSTAN: TENDENCIES AND CONSEQUENCES - RYAZANTSEV, Sergey; PISMENNAYA, Elena; MIRYAZOV, Timur; DUDINA, Olga (CENTRAL ASIA AND THE CAUCASUS, 2019)
The article discusses contemporary tendencies in the export of labor resources from Kyrgyzstan. The issue of seeking employment abroad remains topical for a significant share of the country’s population due to the complicated socio-economic situation and high levels of unemployment and poverty. The major vectors of labor resource export are researched; in recent years, citizens of Kyrgyzstan have increasingly sought employment in Kazakhstan, Turkey, Romania, and South Korea. An assessment of factors that define the Russian Federation as the key receiving country is provided. Most of those working abroad continue to choose Russia, despite the increase in the share of the younger generation that often considers other countries. Young men aged 20-29 with completed high school education currently predominate in the labor migrant flow. The presence of cultural and historic ties, along with tight transport connectivity, has established the framework for the development of close economic relations, including issues related to the export and import of labor resources. The widespread use of the Russian language in the Kyrgyz Republic allows for significant competitive advantages when obtaining employment in various spheres of the Russian economy. An analysis of the structure and number of workers, their distribution across Russian regions, and employment spheres is conducted. A clear eastern vector is apparent in the migration of Kyrgyz citizens to Siberia, the Urals, and the Russian Far East, despite a significant share of workers still being concentrated in the major cities of the European part of Russia. The share of migrants from the Kyrgyz Republic among the working population is currently higher beyond the Ural Mountains, indicating that the Kyrgyz labor force is becoming increasingly needed specifically in the eastern part of Russia. The contribution of labor migration to the economy of the Kyrgyz Republic and the Russian Federation at national and regional levels is studied. Employment opportunities available to Kyrgyz Republic citizens are described. The process of establishing ethnic Kyrgyz community organizations and their influence on the quality of life and labor conditions, as well as on the growth of the number of migrant workers from the Kyrgyz Republic, is discussed. The Kyrgyz Republic’s problems related to labor resource export are analyzed. The outflow of the able-bodied population with active life potential leads to noticeable degradation of the country’s social system. Opportunities for the subsequent development of the Kyrgyz Republic’s economy are brought to light.